PREVENTION EFFECTS OF METHANOLIC EXTRACT OF Eurycoma longifolia ROOTS ON CARBON TETRACHLORIDE-INDUCED HEPATOTOXICY IN RATS - Phebe Hendra; Eustachia Diajeng Wandansari; Elni Meilianti; Bella Anggelina; Damiana Sapta Candrasari; Fenty Fenty (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2019)
The objective of this study was to investigate preventive effects of methanolic extract of Eurycoma longifolia roots (MEEL) against carbon tetrachloride-induced hepatotoxicity in rats. A total of 25 rats were randomly divided into five groups (n=5). Group I was treated with Sodium CMC 1% w/v (peroral, 6 days), and group II was treated with single dose of CCl4 in olive oil (1:1) 2 mL/kg (intraperitoneal injection). Groups III-V received 75, 150, and 300 mg/kg BW of MEEL (peroral, 6 days), respectively, and administration of CCl4 in olive oil (1:1) 2 mL/kg (intraperitoneal injection) on the seventh day. The hepatoprotective potential was estimated by measuring serum activity of biochemical parameters. Further, liver weight ratio and histopathological changes were determined. The serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH) were significantly (p0.05) increased and albumin decreased significantly (p0.05) in the CCl4 treated group, but treatment with MEEL 75 mg/kg significantly (p0.05) prevented the elevation of ALT, AST, and LDH. Histopathological changes also indicated hepatic protection of the MEEL at 75 mg/kg. This finding suggested that methanolic extract of Eurycoma longifolia roots at 75 mg/kg was enough to give a protective effect against CCl4-induced hepatotoxicity